1998
DOI: 10.2134/jeq1998.00472425002700010016x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Soil Phosphorus Solubility with Coal Combustion By‐Products

Abstract: Southern mixed hardwood forest: The former longleaf pine forest. p. 447-494. In W.H. Martin et al. (ed.) Biodiversity of the southeastern United States: Lowland terrestrial communities. John Wiley & Sons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 22 publications
2
66
0
1
Order By: Relevance
“…For instance, Stout, Sharpley, and Pionke (1998) reported fluidized bed coal ash (FBC) and FGD by-product incubation (10 g kg −1 ) with soil reduced WEP by 60% and 50% respectively. Elsewhere, Callahan et al (2002) found that incubation with FBC and FGD (40 g kg −1 ) reduced WEP by at least 50%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Stout, Sharpley, and Pionke (1998) reported fluidized bed coal ash (FBC) and FGD by-product incubation (10 g kg −1 ) with soil reduced WEP by 60% and 50% respectively. Elsewhere, Callahan et al (2002) found that incubation with FBC and FGD (40 g kg −1 ) reduced WEP by at least 50%.…”
Section: Introductionmentioning
confidence: 99%
“…For FGD, which had the greatest and longest-lasting effects on WEP, average soil pH was either significantly lower or not significantly different from the control (Table 3). Stout, Sharpley, and Pionke (1998) and Stout, Sharpley, and Landa (2000) found that the addition of FGD to soil significantly lowered pH, while Callahan et al (2002) found FGD to reduce pH in only one of four acidic soils. At a low soil pH, such as that found in this study, the displacement of Al and Fe from cation-exchange sites and ensuing formation of insoluble Al and Fe phosphates would likely be the major mechanism by which FGD lowered soil WEP concentration.…”
mentioning
confidence: 99%
“…The physical and chemical properties of CCPs depend upon a number of factors, including the origin and the type of coal burnt, boiler conditions, type and efficiency of the emission controls and nature of sorbents used to trap S (Adriano et al, 1980;Stout et al, 1998;Wang et al, 2006), but certain characteristics tend to be similar in most ashes. Chemically, CCPs are mainly (7) silico-aluminate glasses, though some mineral materials may also be present.…”
Section: Properties Of Coal Combustion Productsmentioning
confidence: 99%
“…The remainder is collected at the bottom of the furnace as BA (coarser than FA). Apart from these two ash products, two other by-products -fluidised bed combustion (FBC) ash and flue gas desulphurisation (FGD) ash are produced as part of Clean Coal technologies, mainly to trap sulphur oxides (SO x ) produced during the combustion of high sulphur (S) containing coal (Stout et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Application of gypsum to lower P mobility and reduce leaching of P from agricultural soils is well documented (Stout et al, 1998;Favaretto et al, 2012) and is primarily attributable to enhanced precipitation of Ca phosphates. Such precipitated P is extractable in the 0.5M sodium bicarbonate (pH 8.5) extractant used here since it was developed for to enhance Ca phosphates in calcareous soils (Olsen et al, 1954).…”
Section: Discussionmentioning
confidence: 99%